Cannabidiol in Inflammatory Bowel Diseases: A Brief Overview. (20th July 2012) - Esposito, Giuseppe; Filippis, Daniele De; Cirillo, Carla; Iuvone, Teresa; Capoccia, Elena; Scuderi, Caterina; Steardo, Antonio; Cuomo, Rosario; Steardo, Luca
<x xml:space="preserve">Abstract</x> This minireview highlights the importance of cannabidiol (CBD) as a promising drug for the therapy of inflammatory bowel diseases (IBD). Actual pharmacological treatments for IBD should be enlarged toward the search for low‐toxicityand low‐cost drugs that may be given alone or in combination with the conventional anti‐IBD drugs to increase their efficacy in the therapy of relapsing forms of colitis. In the past, Cannabis preparations have been considered new promising pharmacological tools in view of their anti‐inflammatory role in IBD as well as other gut disturbances. However, their use in the clinical therapy has been strongly limited by their psychotropic effects. CBD is a very promising compound since it shares the typical cannabinoid beneficial effects on gut lacking any psychotropic effects. For years, its activity has been enigmatic for gastroenterologists and pharmacologists, but now it is evident that this compound may interact at extra‐cannabinoid system receptor sites, such as peroxisome proliferator‐activated receptor‐gamma. This strategic interaction makes CBD as a potential candidate for the development of a new class of anti‐IBD drugs. Copyright © 2012 John Wiley & Sons, Ltd.